Piloting short empathetic refutational interview modules in clinical training: Two UK studies - Holford, Dawn; Anderson, Emma C.; Fisher, Harriet; Gould, Virginia C.; Taubert, Frederike; Karlsson, Linda C.; Lewandowsky, Stephan (Elsevier, 2026)
Objective
Our objective was to introduce training in the Empathetic Refutational Interview (ERI), a novel framework for improving vaccine conversations and addressing vaccine misconceptions, as continuing medical education to improve HCPs' vaccine communication confidence.
Methods
We introduced a short-form (60–90 min) ERI training module in two different UK clinical training settings: within a full-length immunisation training day (compared with a control communication module of the same length; Study 1) and as a stand-alone session (Study 2). We conducted a mixed-methods evaluation of training impact on participants' vaccine communication confidence.
Results
Participants were HCPs who attended the training (Study 1: n = 61; Study 2: n = 98). Participants significantly improved their vaccine conversations after training. Control group participants described improved knowledge of information sources as supporting their confidence, while ERI group participants described improved communication skills and techniques. Participants reported that the ERI provided a conversation structure.
Conclusion
Short training modules can improve HCPs' confidence in vaccine communication.